Unlocking Critical Skills: Evaluating Problem-Based Learning in Developmental Biology Education - Pérez Alarcón, Elizabeth Yolanda; Maila Álvarez, María Verónica; Pozo-Rico, Teresa; Gilar-Corbí, Raquel (LUZ, 2025)
This study aimed to assess the effectiveness of Problem-Based Learning (PBL) in enhancing knowledge of active methodologies and skill development among fourth-semester students in Developmental Biology. A PBL intervention program was applied to an experimental group, and results were compared with a control group using structured questionnaires and performance evaluations. Participants were 84 students from the Faculty of Philosophy, Letters, and Education Sciences at Central University of Ecuador. This study utilized a quasi-experimental design with pretest and posttest control groups, analyzed using a General Linear Model. Findings revealed that PBL significantly improved knowledge and experience with active methodologies, as well as critical skills such as explaining phenomena and inquiry. Results also indicated a strengthening of critical thinking and an enhanced ability to seek and evaluate relevant information. These conclusions suggest that PBL is effective for meaningful learning and robust professional development.